Factors Related To Children 1-2 Years Old Developmental Delay In Bululawang Subdistrict, Malang - Siti Kholisah (Journal for Quality in Public Health, 2020)
Child’s developmental delay may related with many factors, one of them is nutritional status, mother’s knowledge about child development, stimulation given by their parents and parenting style. Earlu detection of developmental delay in children aged 102 years old can be done with KPSP. The purpose of this study is to analyze which factors related to children 1-2 years old developmental delay in Bululawang Subdistrict, Malang. Method: The design study was a quantitative research using “cross sectional” approach. The sampling technique was accidental sampling with a sample of 157 respondents. Data was analyzed with logistic regression, significancy (α = 0.05. Results: stimulation (p-value = 0,036) and parental knowledge (p-value = 0,000) are affecting developmental delay 0f 1-2 years old child in Bululawang Subdistrict, Malang, meanwhile nutritional status (p-value = 0,449) is not influencing developmental delay. There is a simoultaneous affect of nutritional status, stimulation, and parental knowledge to developmental delay of 1-2 years old child in Bululawang, Malang (p-value=0,000). Parental knowledge (OR=116,785) is dominant factor that affecting developmental delays followed by stimulation (OR=3,705) and nutritional status (OR=0,676). Conclusion: nutritional status is not related to developmental delay in child aged 1-2 years old, then, stimulation and parental knowledge are related to developmental delay in child aged 1-2 years old in Bululawang Subdistrict, Malang. The dominant factor that related to child developmental delay in Bululawang Subdistrict, Malang is parental knowledge